Factors influencing the decision to use AirAsia’s services - กลิ่นสิงห์ เมธัส; เดชแพง ธรรมรัตน์; หละย้อย พงศ์สิทธิ์; ทุ่มแก้ว จิราพร (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: (1) study the factors influencing passengers’ decision to use AirAsia airline services in Thailand, and (2) analyze the level of importance of each factor affecting passengers’ service selection decisions. The sample consisted of 400 passengers who had used low-cost airline services. A non-probability sampling method using convenience sampling was applied. The research instrument was a questionnaire. Statistical tools used for data analysis included mean, standard deviation, Pearson’s correlation coefficient, and Stepwise multiple regression analysis. The results revealed that, overall, the factors influencing service selection were at a high level. When considering each aspect, price was rated the highest at a very high level, followed by service quality, which was also rated at a very high level, while brand image received the lowest mean score but was still at a high level. In addition, the analysis of the importance of each factor affecting passengers’ decision-making found that price and service quality had the highest level of influence, followed by travel convenience, promotions, and brand image perception, respectively. This indicates that passengers place primary importance on value for money and service standards, which is a key characteristic of consumers in the low-cost airline industry.